Pengaruh Likuiditas, Leverage, dan Kualitas Audit terhadap Audit Report Lag : Studi Empiris pada Perusahaan Sektor Transportation and Logistik yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2018-2022 - Devi Nabila Resti; Jasmi Indra (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine the effect of liquidity, leverage and audit quality on audit report lag in transportation and logistics sector companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period. This research data was obtained through each company's website. This research is a type of causative research. The population in this research is all transportation and logistics companies listed on the Indonesia Stock Exchange. The sampling technique uses purposive sampling. The number of samples in this research was 21 samples. The research results show that: (1) liquidity has a negative and significant effect on audit report lag, (2) leverage has no significant effect on audit report lag, (3) audit quality has no significant effect on audit report lag, and (4) liquidity, leverage , and audit quality together have a significant effect on audit report lag.